Pengaruh Gender Diversity, Dewan Komisaris Independen, Dan Komite Audit Terhadap Pengungkapan Sustainability Report - Pratiwi, Riska Dwi; Isyanto, Puji; Puspitasari , Meliana (CV. ITTC INDONESIA, 2025)
The increasing trend of sustainability report disclosures by companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period raises questions about the effectiveness of corporate governance structures. The low representation of gender diversity in boards of directors and commissioners, the suboptimal oversight function of independent commissioners, and the limited contribution of audit committees have become focal concerns, as these elements are believed to play a crucial role in enhancing the quality, accountability, and transparency of sustainability reporting. This study aims to evaluate the influence of gender diversity in boards of directors and commissioners, independent commissioners, and audit committees on sustainability report disclosure in the banking sector in Indonesia. This study employs a quantitative approach using secondary data obtained from the IDX website and official company websites. The sampling method used is purposive sampling, with a total population of 42 companies observed over a three-year period, resulting in 19 selected companies and a total sample of 57 observations. Data analysis was conducted using IBM SPSS Statistics 27, through classical assumption tests and multiple linear regression analysis. The results indicate that gender diversity in boards of directors and commissioners, as well as the presence of independent commissioners, do not have a significant effect on sustainability report disclosure. In contrast, audit committees show a positive and significant influence on sustainability report disclosure